1999
DOI: 10.1093/jnci/91.17.1459
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Ovarian Epithelial Inflammation in Ovarian Cancer

Abstract: Ovarian cancer is a commonly fatal disease for which prevention strategies have been limited, in part because of a lack of understanding of the underlying biology. This paper reviews the epidemiologic literature in the English language on risk factors and protective factors for ovarian cancer and proposes a novel hypothesis that a common mechanism underlying this disease is inflammation. Previous hypotheses about the causes of ovarian cancer have attributed risk to an excess number of lifetime ovulations or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
340
0
12

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(359 citation statements)
references
References 103 publications
7
340
0
12
Order By: Relevance
“…Early menarche is associated with a more rapid onset of ovulatory cycles, and with the tendency to sustain higher levels of luteal phase estradiol and progesterone (Vihko and Apter, 1984). Thus, a protective effect of late menarche, observed here in premenopausal women, is consistent with hypotheses regarding incessant ovulation (Fathalla, 1971;Casagrande et al, 1979) and ovarian inflammation (Ness and Cottreau, 1999), but inconsistent with the hypothesis that higher levels of progesterone are associated with reduced risk (Risch, 1998). Similar to most previous reports (for example, Hartge et al, 1988;Chen et al, 1992), we found no evidence of an association between age at natural menopause and ovarian cancer risk.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Early menarche is associated with a more rapid onset of ovulatory cycles, and with the tendency to sustain higher levels of luteal phase estradiol and progesterone (Vihko and Apter, 1984). Thus, a protective effect of late menarche, observed here in premenopausal women, is consistent with hypotheses regarding incessant ovulation (Fathalla, 1971;Casagrande et al, 1979) and ovarian inflammation (Ness and Cottreau, 1999), but inconsistent with the hypothesis that higher levels of progesterone are associated with reduced risk (Risch, 1998). Similar to most previous reports (for example, Hartge et al, 1988;Chen et al, 1992), we found no evidence of an association between age at natural menopause and ovarian cancer risk.…”
Section: Discussionsupporting
confidence: 87%
“…The gonadotrophin hypothesis proposes that excessive gonadotropin secretion and consequent increases in oestrogen stimulation lead to proliferation and malignant transformation of ovarian epithelium . More recent hypotheses have suggested a role for chronic ovarian inflammation (Ness, 1999), androgens and progesterone (Risch, 1998), and the possibility that pregnancies reduce risk by clearing transforming cells from the ovaries (ovarian clearance) (Adami et al, 1994). …”
mentioning
confidence: 99%
“…26 In addition, normal ovarian epithelial cells themselves have been previously reported to produce several proinflammatory cytokines, such as monocyte colony-stimulating factor (M-CSF), IL-1, IL-6 and TNF-␣ in response to injury or inflammatory stimuli. 27,28 On the basis of epidemiologic studies, it has been proposed that chronic inflammation may play a role in the development of ovarian tumors, 29 and IL-18 has been considered an important mediator of chronic inflammation in other areas. 30 In keeping with previous reports of IL-18 expression in epithelial layers that line the mucosal surface of the body, we report for the first time that normal ovarian epithelial cells express both IL-18 and ICE and have the potential to produce mature IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated episodes of ovulation-associated injury and repair are presumed to underlie the high frequency of ovarian carcinoma arising from the OSE (Fathalla, 1971;Salazar et al, 1996), which account for 90% of all ovarian cancers (Ozols, 1991). Since ovulation is a natural inflammatory process (Espey, 1980a, b), factors related to inflammation of the OSE have been associated with increased risk of ovarian cancer (Ness and Cottreau, 1999;Ness et al, 2000). It is therefore critically important to understand how inflammatory cell damage is normally resolved in the OSE.…”
mentioning
confidence: 99%
“…Mutations responsible for generating cancerous cells are believed to arise from DNA replication/repair errors during subsequent rounds of OSE cell proliferation. The rate of mutation is further believed to increase in the presence of toxic oxidants that are released during such an inflammatory response (Ness and Cottreau, 1999).…”
mentioning
confidence: 99%